The effect of cyperus rotundus root ethanol extract on the epithelization in the healing process on skin excision wound - Harijadi, Ch. Tri Nuryana E. Suryadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2007)
Ch. Tri Nuryana, E. Suryadi & Harijadi - The Influence of Ethanol Extract of Purple Nutsedge (Cyperusrotundus) on Epithelization of Skin Wound Healing ProcessBackground: If skin is wounded, epithelial cells will migrate to the wound area in order to keep homeostatic.Epithelization consists of mitotic and proliferation of epithelial cells. Rhizome of purple nutsedge (Cyperusrotundus) contains cyperene, flavonoid, Â²-sitosterol dan ascorbic acid that can accelerate epithelization inwound healing process and has been used in traditional medicine.Objective: To investigate the influence of ethanol extract of Purple Nutsedge (Cyperus rotundus) inepithelization of wound healing process.Methods: Fourty five Balb/c male mice 8-10 weeks old, 25-35 g weight, were excised punch biopsy onback 0.5 cm right and left of columna vertebralis, 2.5 cm in cutis from the ear area. The mice weredivided into 5 groups. Negative control group was treated with vehicle of extract, positive control groupwas treated by gel containing placenta extract 1% & neomycin sulfate 0.5% and the others were treatedwith C. rotundus 1%, 2%, and 4% in concentration. Each of the groups was divided into 3 subgroups.Each of the subgroups composed of 3 mice based on the period of termination, i.e.: 3rd, 7th and 12th dayafter wounded. Histological evaluation was done to investigate the thickness of epithelial layer.Results: The data were analyzed by Two-way Anova and the results showed that there was a significantdifference (p<0.05) in every decapitation period, groups, and interaction between decapitation period andgroups. The results of LSD test showed that there was a significant difference (p<0.05) in the thicknessof epithelial layer between negative control and C. rotundus groups.Conclusion: Cyperus rotundus extract accelerates epithelization process of wound healing in mice.Key words: Wound healing - Cyperus rotundus - epithelization - mice